2015
DOI: 10.3846/13923730.2014.890646
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Strip Footing on Reinforced Sand Slope

Abstract: this study evaluated the effects of single, double, and triple reinforcing layers on the bearing capacity ratio (BCR) of strip footing on a sand slope system. Seventy-two laboratory-loading tests were conducted on a stripfooting model on a reinforced sand slope. Moreover, this study illustrated the effects of the different parameters of two reinforcing layers on the bearing capacity of a double-reinforced sand slope. the BCR increased from 1.06 to 3.00 for single-reinforced slope soils, 1.09 to 7.73 for double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
1
1
0
Order By: Relevance
“…Thus, it can be stated that the maximum e/B , for the surface footing, beyond which the slope has a negligible effect on F is 3. Other researchers [9,29,[35][36][37][38][39][40] who investigated the load bearing pressure of a footing on unreinforced and geosynthetic-reinforced slopes reported a trend comparable to the observation made in the present study. They found that the ultimate bearing capacity of the footing improved with increasing the footing edge distance from the crest.…”
Section: Effect Of Footing Edge Distancesupporting
confidence: 89%
“…Thus, it can be stated that the maximum e/B , for the surface footing, beyond which the slope has a negligible effect on F is 3. Other researchers [9,29,[35][36][37][38][39][40] who investigated the load bearing pressure of a footing on unreinforced and geosynthetic-reinforced slopes reported a trend comparable to the observation made in the present study. They found that the ultimate bearing capacity of the footing improved with increasing the footing edge distance from the crest.…”
Section: Effect Of Footing Edge Distancesupporting
confidence: 89%
“…The mechanism of bearing capacity of reinforced footings on sandy soils has been investigated by several experimental studies in the literature. Lab-scale [27][28][29][30][31][32][33][34] and field large-scale [35,36] experiments have been performed to assess the performance of different footings on reinforced weak soils. Reinforcement orientation, as well as the geometry of the footing effects on the bearing capacity of RSF, have been investigated by several researchers.…”
Section: Introductionmentioning
confidence: 99%